Katakis Sebagai Sahabat Perjalanan Iman: Spiritualitas dan Panggilan - Tio, Teodorus (Sepakat : Jurnal Pastoral Kateketik, 2025)
Catechists hold a crucial role in accompanying the faithful on their spiritual journey. This study aims to explore the dimensions of spirituality and the vocational dynamics of catechists within the pastoral context of the Catholic Church, employing a descriptive qualitative approach. Unlike previous studies that primarily emphasized the catechist as a doctrinal instructor, this research highlights the depth of the catechist's personal relationship with Christ as the foundation of their spirituality. The main findings reveal that catechist spirituality manifests in three key dimensions: (1) a contemplative and intimate relationship with Christ as a source of inspiration and strength, (2) a commitment to service that goes beyond institutional routines, and (3) active engagement within the faith community as a space for growth and mission. Furthermore, this study identifies that the awareness of the catechist’s vocation evolves through theological reflection on concrete pastoral experiences—an aspect often overlooked in prior research. These findings underscore the urgency of continuous formation programs that are not only pedagogical but also spiritual and contextual, in order to strengthen the identity and missionary resilience of catechists amid contemporary pastoral challenges.